Modelling gas exchange during platelet storage without agitation. Issue 4 (19th October 2016) - Torres, R.; Tormey, C. A.
Abstract : The aim of this study was to create a model of oxygen distribution within platelet storage bags to evaluate implications of reduced agitation approaches. Based on our model, platelet concentration and surface area most affect internal partial pressure of oxygen, while temperature modifications have least effect, indicating primary potential approaches for optimization of platelet storage with reduced or absent agitation.